Depositional facies and the sequence stratigraphic control of a mixed‐process influenced clastic wedge in the Cretaceous Western Interior Seaway: The Gallup System, New Mexico, USA. Issue 2 (19th November 2019) - Lin, Wen; Bhattacharya, Janok P.
Abstract: Depositional facies have been hypothesized to be linked to sequence stratigraphic positions. Also, shoreline systems are built by mixed processes, including rivers, storms, fair‐weather waves and tides. Resolving the complexity of shoreline deposition requires detailed quantitative facies analysis with particular attention to heterolithic successions. In this study, 71 sections in a 130 km long outcrop belt of the Cretaceous Gallup Formation in the north‐west of the San Juan Basin were measured. Five major facies associations were identified using sedimentological and iconological interpretations, including offshore shelf, non‐deltaic shoreline sandstones, deltas, coastal bayline and fluvial. Each facies association also comprises subordinate facies. Depositional facies interpretations are placed in a high‐resolution sequence stratigraphic framework that allows for reconstructions of the palaeogeography of individual parasequence sets that demonstrate temporal and spatial evolution of facies associations and depositional processes. The results show that the Gallup is a mixed‐process‐controlled depositional system with fair‐weather and storm‐wave dominance, river influence and tide‐effect, contrasting with previous interpretations of a solely fair‐weather wave‐dominated environment. Depositional processes and the resultant facies change with sequence stratigraphic positions in response to relative sea‐level changes – particular facies are only deposited in certain systems tracts. Distinction and transition between non‐deltaic shorefaces and wave‐dominated deltas have also been documented in this study. Non‐deltaic shorefaces are characterized by homogeneous sandstones with a wide‐range bioturbation index and the absence of mudstones. Wave‐dominated deltas are subject to river influence and contain prodelta facies. This study shows the importance of detailed facies analysis with high‐resolution sequence stratigraphic control using outcrops for documenting sedimentary processes of shallow marine shoreline systems.